2011
DOI: 10.1186/1471-2164-12-436
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of high-identity segmental duplications in the grapevine genome

Abstract: BackgroundSegmental duplications (SDs) are blocks of genomic sequence of 1-200 kb that map to different loci in a genome and share a sequence identity > 90%. SDs show at the sequence level the same characteristics as other regions of the human genome: they contain both high-copy repeats and gene sequences. SDs play an important role in genome plasticity by creating new genes and modeling genome structure. Although data is plentiful for mammals, not much was known about the representation of SDs in plant genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…Several Phe ammonia lyase (PAL) genes were clustered on chromosome 16, one group coexpressed in mature/woody organs, and another in vegetative/ green samples, suggesting phenylpropanoid-derived compounds are abundant in both types of samples. The presence of multiple segmental duplications in this region could explain the divergence of PAL gene expression profiles within the cluster (Giannuzzi et al, 2011). The coexpression of neighboring genes with apparently uncorrelated functions was observed in both vegetative/green and mature/woody samples, which contrasts with the coexpression analysis data covering the entire data set.…”
Section: Gene Coexpression Dynamics Contribute To the Division Betweementioning
confidence: 80%
“…Several Phe ammonia lyase (PAL) genes were clustered on chromosome 16, one group coexpressed in mature/woody organs, and another in vegetative/ green samples, suggesting phenylpropanoid-derived compounds are abundant in both types of samples. The presence of multiple segmental duplications in this region could explain the divergence of PAL gene expression profiles within the cluster (Giannuzzi et al, 2011). The coexpression of neighboring genes with apparently uncorrelated functions was observed in both vegetative/green and mature/woody samples, which contrasts with the coexpression analysis data covering the entire data set.…”
Section: Gene Coexpression Dynamics Contribute To the Division Betweementioning
confidence: 80%
“…Whole-genome duplication and segmental duplication events are the primary origin of new gene functions during the evolution of plants, allowing an increase in biological complexity56. Accordingly, several of the grapevine ATL genes appear to originate from tandem duplication events and others from whole-genome duplication, and the retention of the duplicated genes probably reflects the fixation of adaptive mutations that have diversified the corresponding protein functions (subfunctionalisation).…”
Section: Discussionmentioning
confidence: 99%
“…The highly similar genes may be merged into the same sequence during genome assembly, even if Sanger technology with its long read was used. That is especially true for the polyploidized genome of grape, where three ancestral genomes contribute to the haploid content (Jaillon et al, 2007;Velasco et al, 2007;Giannuzzi et al, 2011). The estimated number of grape genes is about 30,000, but EST records showed that a minimum of about 40,000 genes are present in Vitis spp.…”
Section: Polymorphismmentioning
confidence: 99%